Determinants of training motivation: a case of non-managerial level employees in value added tea company - Rebecca, E.; Bandara, M.M.M.; Weerasinghe, T.D.; De Alwi, A.C. (University of Jaffna, 2016)
The purpose of this study is to investigate the factors which determine the employees' participation in training programs in one of the Tea Manufacturing Companies in Sri Lanka. Even though non-managerial level employees in the aforesaid company have requested several training programs from their supervisors semi-annually, they are reluctant to participate in those programs. Hence, this research is conducted as an exploratory field study which is cross-sectional, intending to explore the determinants of training motivation of employees in the selected company. Unit of analysis of the study is at the individual level; individual non-managerial employees. Researcher administered a standard questionnaire to collect primary data from a sample of 83 non-managerial employees where convenience sampling was used to select the sample. Exploratory Factor Analysis (EFA) was conducted to find out the significant determinants of training motivation. Moreover, factor loading values and cumulative percentage of extraction sums of squared loading values were used to draw the conclusion. It is found that self-efficacy, training reputation and job benefit are the significant training motivators for non-managerial employees in the selected company while supervisory support and the financial sponsorship were found to be insignificant motivators. Hence, it is recommended for practicing manager and Human Resource (HR) professionals in the selected domain to design training programs which will improve the efficacy and the reputation of the participant, and especially, to deliver transferable skills in designing future training programs.
Keywords: Non- managerial employees; Training motivators; Training participation